A rare case report: isolated midbrain lacunar infarct affecting the ipsilateral medial longitudinal fasciculus causing internuclear ophthalmoplegia effect - Sheik, Sanaulla; Azeez, Maktoum; Gafoor, Biju; Kolleri, Jouhar (International Journal Of Community Medicine And Public Health, 2023)
Isolated medial longitudinal fasciculus infarct is rare and can also be associated with cranial nerve nuclei or extra-nuclear regions leading to respective neurological deficit. We report a case of 73-year-old woman presenting with a 24 hour of confusion, abnormal eye movement and unsteady gait on a background history of uncontrolled diabetes mellitus (DM), hypertension and Alzheimer’s disease. Her examination found to have dysdiadokinesia in left upper limb and inability to adduct right eyeball on left lateral gaze, without affecting the pupil. She was not oriented to time and place while before this event she could. Her examination found to have normal power in limbs and sensation. Her computed tomography (CT) brain showed no evidence of acute infarction or intracranial bleed. Magnetic resonance imaging (MRI) brain demonstrated acute lacunar infarct involving the ipsilateral medial longitudinal fasciculus. This case demonstrates rare brainstem infarct affecting medial longitudinal fasciculus region below the IIIrd cranial nerve nucleus giving features of internuclear ophthalmoplegia affecting medial rectus muscle without affecting autonomic fibres of IIIrd cranial nerve due to which the pupil is not affected. We recommend strict control of predisposing conditions, mainly diabetes and hypertension to reduce the incidence of brainstem stroke.